(untitled) (Innovative professional education, 2024)
The work defines the requirements and tasks of ensuring quality education at the international, state and institutional levels; the importance of quality vocational education for sustainable global development and recommendations for its achievement are highlighted; the essence of the concept of digitalization is revealed, the main principles of the development of the digital economy and society of the state are named, and proposals are made to ensure the quality of vocational training of specialists in the conditions of the implementation of digitalization in the educational sector.